Strategi Peningkatan Nilai Tukar Petani Terhadap Tingkat Kesejahteraan Peternak Kambing di Kabupaten Sidoarjo - Risqi Firdaus Setiawan; Nisa Hafi Idhoh Fitriana; Pawana Nur Indah (Universitas Udayana, 2022)
This study aims 1) To determine the level of welfare of goat breeders and 2) To determine the strategy of increasing the exchange rate of goat breeders in Sidoarjo Regency. Among them by calculating the exchange rate of farmers to determine the level of welfare of goat breeders and analyze the strategy of increasing the exchange rate of rice farmers. The research location was determined by purposive sampling method in 2 sub-districts in Sidoarjo Regency which is the center for goats. This study uses primary data obtained from goat breeders through direct interviews using a list of questions that have been prepared in advance. Samples were selected by purposive random sampling as many as 30 goat breeders. The data analysis method used is analysis with the mathematical formula NTP = IT/IBx100, the NTP indicator with criteria ntp>100 has a surplus, ntp=100 breaks even, ntp<100 has a deficit and the SWOT analysis method. The results showed that the exchange rate of goat breeders in Sidoarjo Regency in 2020 increased by 4.10 percent from 113.22 in 2019 to 117.32 in 2020. This indicates that goat breeders in Sidoarjo Regency are experiencing a surplus or prosperity. In the strategy of increasing the exchange rate of goat farmers using the SWOT method is an aggressive strategy which is a very profitable situation.